The change pattern of CSR ecological strategy of trees and seedlings during different succession stages in tropical lowland rainforests - Wen, Yabo; Chen, Chen; Sun, Tianxu; Yang, Yuwei; Han, Xuejiao; He, Baohui; Lu, Xinghui (Frontiers in Forests and Global Change, 2023)
Monitoring changes to growth-survival strategies is beneficial during plant growth and development to understand the dynamics of community succession. We measured key leaf traits and calculated competition, stress-tolerance, and ruderals ecological strategy scores for trees and seedlings in different successional stages in tropical lowland rain forests. We analyzed functional trait patterns and CSR strategies with plant growth and development through the different succession stages. We found that trees used strategies that were shifted from S/CS and CS strategies to CS/CSR strategies along the succession. However, seedlings maintained the use of the S/CSR strategy. Seedlings showed lower leaf dry matter content), higher specific leaf area, and their leaf area was relatively conservative. We also observed that the functional traits of seedlings and large trees showed basically consistent changes through each succession stage. Using the standard deviation of C-, S-, and R-scores, we found that the ecological strategy width of trees is smaller, while seedlings have a wider range of ecological strategies. Together, this information can be used to define plant succession changes with functional plant trait changes using different CSR ecological strategies in tropical rainforests that are a threated due to human activities. The research results provide scientific basis for understanding the strategic change of plant growth and predicting the direction of forest function succession, and also provide theoretical support for the management of tropical lowland rainforest in China.